Real-world procedural and clinical outcomes of contemporary balloon-expandable and self-expandable TAVR systems: a single-center experience - Vinciguerra, Mattia; Spadafora, Andrea; Iaccarino, Alessandro; Miraldi, Fabio; Vitagliano, Eduardo; De Bellis, Antonio; Greco, Ernesto (Frontiers in Cardiovascular Medicine, 2026)
BackgroundTranscatheter aortic valve replacement (TAVR) is rapidly becoming the preferred treatment for patients with severe aortic stenosis across different surgical risk profiles. However, the comparative performance of contemporary balloon-expandable valves (BEVs) and self-expandable valves (SEVs) in real-world practice remains debated.ObjectivesTo evaluate procedural and postoperative outcomes associated with different contemporary TAVR systems in a consecutive cohort of patients treated at a single center.MethodsWe retrospectively analyzed 366 consecutive patients with symptomatic severe aortic stenosis and high surgical risk who underwent TAVR at Casa di Cura San Michele (Maddaloni, Italy) between January 2019 and October 2024. Patient baseline characteristics, procedural data, and in-hospital outcomes were collected and compared across different TAVR systems.ResultsAmong implanted prostheses, 71.0% were SEVs (Accurate Neo, Evolut R/Pro, Portico, Allegra) and 28.7% were BEVs (Sapien 3, Myval). BEVs were associated with significantly higher post-procedural transvalvular gradients (11.7 vs. 8.5 mmHg, p < 0.0001) but a lower incidence of moderate-to-severe paravalvular leak (2.9% vs. 6.9%). The need for permanent pacemaker implantation was more frequent in the BEV group (11.4% vs. 6.5%). Overall in-hospital mortality was 2.7%. Device success was achieved in 93.2% of procedures.ConclusionIn a real-world, single-center cohort, both BEVs and SEVs provided favorable outcomes. While BEVs demonstrated superior sealing properties with fewer paravalvular leaks, SEVs were associated with lower postoperative gradients. Careful consideration of anatomical and procedural factors remains essential for optimizing outcomes with contemporary TAVR systems.